Soil Quality and Health to Assess Agro-Ecosystems Services - Sara Marinari; Emanuele Radicetti; Roberto Mancinelli (Agriculture, 2022)
Nowadays, agricultural production systems are facing serious challenges mainly related to the climate changing, the world population growing and environmental pollution that are threatening the survival of the natural resources [...]